Race, Ethnicity and Nuclear War Representations of Nuclear Weapons and Post-Apocalyptic Worlds - Williams, Paul (Liverpool Science Fiction Texts and Studies, 2011)
Ranging across novels and poetry, critical theory and film, comics and speeches, Race, Ethnicity and Nuclear War: Representations of Nuclear Weapons and Post-Apocalyptic Worlds explores how writers, thinkers, and filmmakers have answered the following question: are nuclear weapons 'white'? Race, Ethnicity and Nuclear War listens to voices from around the Anglophone world and the debates followed do not only take place on the soil of the nuclear powers. Filmmakers and writers from the Caribbean, Australia, and India take up positions shaped by their specific place in the decolonizing world and their particular experience of nuclear weapons.The texts considered in Race, Ethnicity and Nuclear War encompass the many guises of representations of nuclear weapons. New thoughts are offered on the major texts that SF scholars often return to, such as Philip Wylie's Tomorrow! and Pat Frank's Alas Babylon, and a host of little known and under-researched texts are scrutinized too.